Golimumab pharmacokinetics in ulcerative colitis: a literature review. (January 2017) - Harzallah, Ines; Rigaill, Josselin; Williet, Nicolas; Paul, Stephane; Roblin, Xavier
Golimumab (GLM) is the latest anti-tumor necrosis factor (TNF) that gained its marketing license. Thanks to the PURSUIT induction and maintenance trials, it was approved for the treatment of ulcerative colitis (UC) in 2013. The other anti-TNF drugs available are infliximab and adalimumab. These two drugs have validated algorithms concerning prescription and therapeutic drug monitoring (TDM) but little is known about GLM. The available data on GLM's exposure–response relationship in UC are from the PURSUIT trials and are recently published. The data reveal all the factors that may impact the pharmacokinetic (PK) parameters: dosage, body weight (BW), concomitant drugs, the presence of anti-drug antibodies (ADAbs), sex and age. In addition, the GLM trough level at steady-state appears to be correlated with the patient's improvement which may make it a precious indicator to predict the clinical response. There is, however, no consensus on a possible therapeutic level or cutoff associated with clinical response, remission, or any other outcome measure such as endoscopic healing in UC. This lack of a threshold value, and its validation with different assay techniques, makes it difficult to use GLM TDM in clinical practice. As with other anti-TNF agents, GLM is associated with development of ADAbs, of which the prevalence and effects are still insufficiently described. The objective of this review is to describe current data and understanding of the PK of GLM including serum concentrations of GLM and ADAbs in UC patients. Better understanding of these parameters could lead to improved patient care with GLM.